SUSTAINABILITY BY DESIGN: HOW NEO BANKS ARE PIONEERING ECO-FRIENDLY FINANCIAL SERVICES – AN EMPIRICAL STUDY (Lex localis - Journal of Local Self-Government, 2024)
This empirical study looks at how neo banks are embedding sustainability in what they do in terms of financial services and also how in turn customers react to these eco-friendly changes. As the world’s focus turns more and out attention to environmental issues neo banks are at the fore front of green finance which includes paperless transactions, digital know your customer processes, ethical investment options, and carbon neutral business practices. We look at the issue of customer awareness of sustainable finance options, what they think of the green innovations, digital ease of use, and the end their level of satisfaction with neo bank services. We collected data from 120 respondents via a structured questionnaire and analyzed it with correlation and regression tools. What we found is that green innovation and ethical awareness are key drivers of customer’s sustainability related perceptions and their overall satisfaction. We put forth that sustainability by design is a key strategy for neo banks which in turn grows customer loyalty and environmental responsibility.